Prospective Associations Between Play Environments and Pediatric Obesity. Issue 4 (May 2019) - Fitzpatrick, Caroline; Alexander, Stephanie; Henderson, Melanie; Barnett, Tracie A.
Purpose: To identify school typologies based on the availability of play equipment and installations. We also examined the associations between availability of play items and child adiposity. Design: Secondary analysis of longitudinal data. Setting: Elementary schools in Montreal, Canada. Participants: We used data from the Quebec Adipose and Lifestyle Investigation in Youth study (QUALITY), an ongoing investigation of the natural history of obesity and type 2 diabetes in Quebec children of Caucasian descent. Measures: The presence of play items was assessed in each child's school. A trained nurse directly assessed child anthropometric measurements to derive body mass index and waist circumference. Body fat composition was measured using DEXA Prodigy Bone Densitometer System. Analyses: The final analytic sample comprised 512 students clustered in 296 schools (81% response). We used K-cluster analyses to identify school typologies based on the variety of play items on school grounds. Generalized estimation equations were used to estimate associations between school clusters and outcomes. Results: We identified 4 distinct school typologies. Children in schools with the most varied indoor play environments had lower overall body fat, B = −1.26 cm (95% confidence interval [CI], −2.28 to −0.24 cm), and smaller waist circumference, B = −4.42 cm (95% CI, −7.88 to −0.96 cm), compared to children with the least varied indoor play environment. Conclusion: Our results suggest that policies regulating the availability of play items in schools may enrich comprehensive school-based obesity prevention strategies. Extending research in this area to diverse populations is warranted.